2014
DOI: 10.1186/1471-2415-14-86
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of surgical management for giant retinal tear more than 180°

Abstract: BackgroundTo evaluate the surgical outcome for management of giant retinal tear (GRT) more than 180° by combined pars plana vitrectomy (PPV), encircling scleral buckle, 360° Laser endophotocoagulation, and silicon oil tamponade.MethodsThis was a Prospective, interventional case series study. Twenty four eyes of 23 patients suffering from GRT more than 180° underwent PPV combined with encircling scleral buckle and 360° laser retinopexy of the peripheral retina followed by silicon oil tamponade. All patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
3
19
0
3
Order By: Relevance
“…Similarly the extreme poor preoperative visual acuity noted in this group is similar to that documented in another study from Egypt [4]. In this study on GRT reported by sheriff; of the 24 participating eyes, only 3 eyes with attached macular had a readable visual acuity.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similarly the extreme poor preoperative visual acuity noted in this group is similar to that documented in another study from Egypt [4]. In this study on GRT reported by sheriff; of the 24 participating eyes, only 3 eyes with attached macular had a readable visual acuity.…”
Section: Discussionsupporting
confidence: 89%
“…Idiopathic GRT, which has been noted as the commonest etiology by other studies, also occurred in the majority of eyes in this study [4] [5].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…While most commonly gas is used as an endotamponade during standard vitrectomy surgery, silicone oils have shown good post-operative results in the treatment of persistent macular holes [3] and especially in more complicated procedures such as giant retinal tear [4] and patients with retinal detachment due to proliferative diabetic retinopathy [5] and proliferative vitreopathy [6]. Usually, air or expanding gases are used as an endotamponade for macular holes in vitrectomy surgery [7][8][9].…”
Section: Introductionmentioning
confidence: 99%